2022
DOI: 10.5194/jbji-7-241-2022
|View full text |Cite
|
Sign up to set email alerts
|

Mycetoma caused by Madurella mycetomatis in immunocompromised patients – a case report and systematic literature review

Abstract: Abstract. The aim of this study was to review the available literature concerning Madura foot (“mycetoma”) caused by Madurella mycetomatis in immunocompromised patients. With a systematic literature search, we identified only three papers, describing a total of three immunocompromised patients. Hence, the clinical presentation and prognosis of the disease in this patient population have not yet been well described. In addition, we present a case from our institution, illustrating the complexity of the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The presence of bone marrow edema without obvious cortical involvement or bone destruction can represent early involvement. Hoogervorst LA et al (29) reported noncontiguous disseminated small hypointense lesions scattered within the tibial bone marrow in an immunocompromised patient without any bone involvement. Advanced long term disease results in extensive osteolysis, sclerosis and bony ankylosis (23).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of bone marrow edema without obvious cortical involvement or bone destruction can represent early involvement. Hoogervorst LA et al (29) reported noncontiguous disseminated small hypointense lesions scattered within the tibial bone marrow in an immunocompromised patient without any bone involvement. Advanced long term disease results in extensive osteolysis, sclerosis and bony ankylosis (23).…”
Section: Discussionmentioning
confidence: 99%